Telemedicine in nutritional management of children with severe neurological impairment: implication for quality of life - Tagi, Veronica Maria; Eletti, Francesca; Dolor, Jonabell; Zuccotti, Gianvincenzo; Montanari, Chiara; Verduci, Elvira (Frontiers in Nutrition, 2024)
Children with severe neurological impairment (SNI) frequently present feeding problems requiring a close monitoring of their nutritional status. In addition to constant clinical monitoring of body composition and nutritional indexes in these patients, frequent reports of dietary intake and weight gain variations are useful to ensure proper nutritional management. Furthermore, non-oral feeding is often needed to avoid malnutrition or aspiration pneumonia, constantly necessitating medical assistance. Despite their necessity for frequent hospital accesses, these patients' disabilities represent an important obstacle to accessing care, generating anxiety and concern in children and their families. Telemedicine has proven to be a promising instrument for improving paediatric patients' healthcare in several fields. By breaking down geographical and temporal barriers, telehealth may represent a valuable tool to implement in clinical practice, in order to improve patients' outcomes and quality of life. The aim of this narrative review is to provide an overview of the main nutritional issues in children with SNI, the potential implications of telemedicine in their management and the available evidence regarding the effects and benefits of telehealth.